Export Markets for Distillers Grains - Fox, John A. (North American Institute for Beef Economic Research, 2010)
Spurred by the introduction of renewable fuel standards and the elimination of MTBE as a gasoline additive, U.S. production of fuel ethanol expanded from about 1.6 billion gallons in 2000, to 9 billion gallons in 2008. This increase has led to questions about whether markets could absorb the concomitant increase in production of distillers grains (DG). To date most DG has been used in the domestic cattle and hog sectors, but DG exports have been growing. This fact sheet examines recent trends in DG exports from the U.S.